2014
DOI: 10.3748/wjg.v20.i10.2641
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate ameliorates indomethacin-induced gastrointestinal mucosal injuryviainhibiting translocation in rats

Abstract: These results indicate that AL-Na ameliorates non-steroidal anti-inflammatory drug-induced small intestinal enteritis via bacterial translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
4
25
2
Order By: Relevance
“…Dengiz, Odabasoglu, Halici, Cadirci, and Suleyman () found increased CAT activity in indomethacin‐induced gastric ulcer. Yamamoto, Itoh, Nasu, and Nishida () found decreased GPx activity as parallel to our study, but reported diminished CAT and SOD activities in indomethacin‐induced small intestinal injury. An elevated activity of CAT and SOD were observed in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dengiz, Odabasoglu, Halici, Cadirci, and Suleyman () found increased CAT activity in indomethacin‐induced gastric ulcer. Yamamoto, Itoh, Nasu, and Nishida () found decreased GPx activity as parallel to our study, but reported diminished CAT and SOD activities in indomethacin‐induced small intestinal injury. An elevated activity of CAT and SOD were observed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Dengiz, Odabasoglu, Halici, Cadirci, and Suleyman (2007) found increased CAT activity in indomethacin-induced gastric ulcer. Yamamoto, Itoh, Nasu, and Nishida (2014) of protein damage. Vit C, Vit E, β-carotene, Se combination, and also ranitidine were found to attenuate indomethacin-induced effects, probably due to halting of the deleterious effect of free radicals (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of experimental studies on NSAID-enteropathy have used single, highdose indomethacin administration to induce mucosal damage. In these models, the injury pattern consists mainly of multiple, hemorrhagic lesions involving the full thickness of intestinal wall [48,49,50], a picture that differ greatly from the ones seen at enteroscopy or video capsule endoscopy in patients taking NSAIDs chronically [11,12,13]. Most importantly, these acute models of intestinal damage may be not suitable to evaluate the protective effect of poorly absorbed antibiotics, like rifaximin, which need at least 7-10 days to consistently affect intestinal bacterial load, composition and activity [51].…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup of animals, treatment with rifaximin was initiated 7 days before starting indomethacin administration and continued for 14 days until the end of treatment with the NSAID. The dose of 50 mg/kg BID had been found to protect against enteropathy induced by indomethacin in a preliminary dose-response study (25,50 and 100 mg/kg BID). In addition, the selected rifaximin dose was similar to that employed in previous studies in rats [38,39].…”
Section: Experimental Designmentioning
confidence: 99%
“…For example, nonsteroidal anti-inflammatory drugs (NSAIDs) are known to damage both gastric and intestinal mucosa. MUC2 expression in intestinal mucosa has been reported to be reduced by mucosal damage caused by NSAIDs [21]. Additionally, intestinal mucosal damage by NSAIDs reduces the number of intestinal microvilli, disrupts the epithelial surface, and opens tight junctions, leading to increased intestinal permeability [22].…”
Section: Toxicological Evaluationsmentioning
confidence: 99%